Analisis Kecemasan (ANXIETY) Mahasiswa Selama Pembelajaran Daring - Fergi Syuhada; Syarifah Jihan Nabila; Tara Aulia; Yuliana Nelisma; Dara Hafiza (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to identify and analyze the forms of anxiety experienced by students during online learning. Anxiety is a complex emotional response, involving interactions between cognitive, affective, and psychomotor factors. The instruments used in this study were compiled based on the theories of David Barlow, Lazarus, and David Sue. The results show that anxiety can appear in various forms such as fear of uncertainty, difficulty in managing emotions, and avoidance of social situations. This study is expected to be the basis for providing effective Guidance and Counseling services in the context of online learning.